PERANCANGAN SISTEM INFORMASI PENGEMBANGAN POTENSI PARIWISATA SUMBER BOTO DI KABUPATEN JOMBANG BERBASIS WEB MENGGUNAKAN METODE RESEARCH AND DEVELOPMENT - Mohammad Fikri Agus Setiawan; Chamdan Mashuri; Ginanjar Setyo Permadi; Ahmad Heru Mujianto (Fakultas Teknologi Informasi, 2025)
In the current digital era, the use of information and communication technology is very important to support the development of the tourism industry. Utilization of web-based information systems can be an effective solution to overcoming the problem of lack of information. Web-based information system provides accurate, complete and up-todate tourist destination information and can be accessed by anyone, anytime, anywhere.to ensure the development of information systems that are appropriate and in accordance with user needs, a research and development (r&d) approach was chosen in this research. The r&d approach includes a series of systematic steps starting from initial research to understand needs and problems, to system design and development, to system evaluation and improvement. With this approach, it is hoped that the resulting information system can become an effective means of promoting and increasing the tourist attraction of sumber boto. Sumber boto is a natural tourist destination with unspoiled natural beauty, clear water flow and a calm and cool atmosphere. This natural beauty is a special attraction for tourists who want to enjoy natural beauty and seek tranquility, far from the noise and hustle and bustle of the city. Tourism is one of the industries that has a strategic role in encouraging economic growth in a region. This sector not only helps increase regional income but also creates jobs and improves the welfare of local communities. Keywords: Information Systems, Research and Development Methods, Sumber Boto Tourism